Filosofia e direito: a filosofia da consciência e o fenômeno jurídico - Traesel, Clório Erasmo (Universidade do Vale do Rio dos Sinos, 2011)
History provides, to a certain extent, a report of the society in which it is involved at the present. It is in that which is the possibility of responses to certain concerns, without which such answers exceeds its condition of answers to solutions. But looking at History is, in fact, look at the structure and the various "texts" that forms it. The various "events" should be considered in this context. In the course of History, time and space in the West, it has always been seen as a succession of steps, steps seen as changes which, in its turn, resulted from choices and omissions.The latter, if not morally, ideologically superior to the former. To be possible this narrative, it is necessary a philosophical conceptual framework that could represent and justify the values involved in the choices: Philosophy. From the Greek philosophy, is a mainstay justifier that permeated all the other institutions, especially the State and the Law. Effectively the choices are made; what predominates, however, never resigns from his previous experience, because there is absolutely nothing of originating. The event, being it the State, being it the Law, is always linked to the context. A context of actions, attitudes, culture, in a wide sense involving all behaviors, ways of thinking and acting of the human being, involving the ethos, that is original. In fostering the culture that it is possible to observe the value of the actions. The value assigned to them is the criteria used to make the choices and configures, therefore the ethical and mythical nucleus in both space and time of Western civilization. If since always one is in a world of choices, since always is in a practical world. Philosophy, however, turned into metaphysics, hides this original question of choice, splitting the reason and subordinating practical reason to theoretical reason, in so far as that it provides the necessary structural elements (transcendent) for the formulation of judgments. Split the reason is a choice, linked to a way of acting, to an attitude, to an ethos. This is reflected in the way history is considered (successive and superior stages) and the philosophical foundation of the State and Law. The example of Modernity is eloquent, thus the pretext of overcoming the Medieval period, recovers materials of classical antiquity, without realizing, however, that the Medieval period even broken with the antiquity. Thus, it is possible to look at History not in the linearity of the succession of phases and periods, but as a cultural unfolding in definite space. This point of view allows the identification of the political demonstrations (state) and legal (law) the nature of the choices from the philosophical foundation. State and Law, although being conquests (in the positive sense) of Western civilization, retain the originating of ethos civilization. The unveiling is possible from the hermeneutic philosophy or of philosophical hermeneutics. Remove the veil that covers the relationship, not only reveals the many social problems, but it is implicit a contradiction: it remains a discourse that replaces the reality (the sole one) by the appearance (equality between the one and another) and the truth, indeed, is given to rhetoric, to the argument.The philosophical hermeneutics is not normative, but only through it is possible to say that since one is always in practical reason, one always makes choices, in the History and Language.
Keywords: Hermenêutica; Razão prática; Razão teórica; Filosofia e Direito; História e filosofia; Hermenêutica filosófica; Filsofia da consciência; Hermeneutics; Philosophical hermeneutics; The philosophy of consciousness; Practical reason; Theoretical reason; Philosophy and law; History and Philosophy; ACCNPQ::Ciências Sociais Aplicadas::Direito